(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Epiretinal membranes are avascular, fibrocellular membranes which develop on the inner most layer of the retina. These membranes can be idiopathic or secondary to the silicone oil injection after pars plana vitrectomy in patients with rhegmatogenous retinal detachment. When symptomatic, such membranes can cause decreased vision, visual distortion and sometimes diplopia. The purpose of this study was to compare the idiopathic epiretinal membranes versus silicone oil filled eyes epiretinal membranes in terms of their diagnostic and surgical features. Material and methods: The study was conducted at the Department of Ophthalmology, Services Hospital Lahore where 13 eyes with idiopathic epiretinal membranes (ERMs) and 13 eyes with silicone oil filled eyes epiretinal membranes (SOERMs) were evaluated from August 2017 to April 2019. The main diagnostic outcome was the preoperative Optical Coherence Tomographic (OCT) findings and main surgical outcome was peroperative time required for removal of epiretinal membranes. Results: Mean central retinal thickness of patients with SOERMs on OCT was 530.30µm, which was recorded one day before surgery. It was greater as compared to the central retinal thickness in patients with idiopathic ERMs which was 391.92 µm. The mean time required for the removal of SOERMs was 466.38 seconds. It was longer as compared to the time required to remove idiopathic ERMs which was 385.69 seconds. Conclusion: The SOERMs are relatively difficult to remove due to increased thickness and more adherent nature as compared to idiopathic ERMs which were single layer and relatively easy to remove.